Biocompatibility evaluation of a thermoplastic rubber for wireless telemetric intracranial pressure sensor coating. (May 2015) - Yang, Jun; Charif, Andrea C.; Puskas, Judit E.; Phillips, Hannah; Shanahan, Kaitlyn J.; Garsed, Jessica; Fleischman, Aaron; Goldman, Ken; Roy, Shuvo; Luebbers, Matthew T.; Dombrowski, Stephen M.; Luciano, Mark G.
Abstract: This study investigated the biocompatibility of the experimental thermoplastic rubber Arbomatrix ™ that will be used as the protective coating on a novel intracranial pressure (ICP) sensor silicon chip. Arbomatrix ™ was benchmarked against biocompatible commercial silicone rubber shunt tubing in the brain via a rat model with 60-day implant duration. A bare silicon chip was also implanted. The results showed similar cellular distribution in the brain–implant boundary and surrounding tissues. Quantitative analysis of neuron and glia density did not show significant difference between implants. Through histological and immunohistochemical evaluation we conclude that Arbomatrix ™ is well tolerated by the brain. Due to its exceptional barrier properties Arbomatrix ™ has already been shown to be an excellent protective coating for new ICP monitoring chip.